Decision Support System Determining Majors at Islam Kader Bangsa Vocational School using the SAW Method - Intan Permatasari (Institute of Computer Science, 2020)
Decision Support System (DSS) is a computer-based system that can be used to assist someone in improving performance in making decisions. By using SPK, it is hoped that it can help decision making in solving problems to determine majors at the Kader Bangsa Islamic Vocational School. In this study, a decision support system will be developed using a method that can solve the Multiple Attribute Decision Making (MADM) problem which is proven to have very effective performance on data whose values ​​are in the form of a range within a certain value range. The DSS method used in this research is Simple Additive Weighting (SAW). This method determines the weight value for each attribute, which is followed by a ranking process. So that it will produce the best alternative from many alternatives with fairly precise calculations. The alternative is prospective new students at the Kader Bangsa Islamic Vocational School who will be selected based on predetermined criteria.